Kajian Aspek Interior Kantor (Studi Kasus : Pt. Balai Diklat Perkretaapian): ## - Irwansyah, Irwansyah; Giovani, Giovani (Waca Cipta Ruang, 2020)
The office is a place used for business or can be referred to as the "Company" which is run regularly. Offices are divided into two types, namely large offices or so-called headquarters and simple offices or so-called branch offices. A pleasant office is a place that is not boring and can excite work. Balai Diklat Perkretaapian is the office where the work unit under the Badan Pengembangan Sumber Daya Manusia engaged in railway services. The problems and arrangements in this office vary from the lighting, the condition of the room, and the arrangement of furniture that affects the interior room. Physically, the interior of today's office is more needed in an open and intimate atmosphere. Proper application of color and light can eliminate existing dark corners. Massive walls can be reduced by placing transparent glass on some sides of the space so that the impression is wide and open. This problem is considered important to be solved and given a solution by making a study of the interior aspect of the office. The goal is to optimize the workspace in order to be able to restore the passion of the employees who work in it and give a first impression that is scarred to the client. Keywords: Aspects, Elements, Interior Design and Office